Cellular polyamines modulate mRNA stability. (3rd October 2017) - Chai, Haoxi; Yang, Wannian; Shi, Huazhong
ABSTRACT: Polyamines (PAs) are polycationic compounds found in all living organisms and play crucial roles in growth and survival. PAs interact with and modulate the functions of anionic macromolecules such as DNA, RNA and proteins. LHR1/PUT3 is a polyamine influx transporter localized in the plasma membrane in Arabidopsis. In our recent paper in The Plant Journal, 1 we demonstrated that LHR1/PUT3 has a pivotal role in stabilizing the mRNAs of several important heat stress responsive genes under high temperature. In this short communication, we discuss about a putative pathway for modulating the PUT3 transport activity and the significance of evolutionary variations in PUT3 in Arabidopsis.